2023
DOI: 10.1073/pnas.2214655120
|View full text |Cite
|
Sign up to set email alerts
|

CO 2 -forced Late Miocene cooling and ecosystem reorganizations in East Asia

Abstract: In parallel with pronounced cooling in the oceans, vast areas of the continents experienced enhanced aridification and restructuring of vegetation and animal communities during the Late Miocene. Debate continues over whether p CO 2 -induced global cooling was the primary driver of this climate and ecosystem upheaval on land. Here we present an 8 to 5 Ma land surface temperatures (LST) record from East Asia derived from paleosol carbonate clumped isotopes and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A. arguta flourished for millions of years since its birth, experienced the first intraspecific divergence during the late Miocene global cooling, and formed the basic pattern of Northern and Southern groups ( Zachos et al., 2001 ; Wen et al., 2023 ). As the two groups diverged further, A. arguta formed more phylogeographic subgroups, in which the Northern group showed higher genetic differentiation than the Southern group ( Supplemental Figure 10A and 10B ).…”
Section: Discussionmentioning
confidence: 99%
“…A. arguta flourished for millions of years since its birth, experienced the first intraspecific divergence during the late Miocene global cooling, and formed the basic pattern of Northern and Southern groups ( Zachos et al., 2001 ; Wen et al., 2023 ). As the two groups diverged further, A. arguta formed more phylogeographic subgroups, in which the Northern group showed higher genetic differentiation than the Southern group ( Supplemental Figure 10A and 10B ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this is not indicative of differences in evolutionary age of C 4 photosynthesis. In both, C 4 grasses and C 4 eudicots, the age of C 4 origins spans from the Oligocene to the Pleistocene with most origins dating back to the Late Miocene (see Sage, 2017 for a summary), an era of global expansion of C 4 vegetation due to declining atmospheric CO 2 combined with global cooling and increase in climate seasonality and aridity (Cerling et al., 1997 ; Wen et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this is not indicative of differences in evolutionary age of C 4 photosynthesis. In both, C 4 grasses and C 4 eudicots, the age of C 4 origins spans from the Oligocene to the Pleistocene with most origins dating back to the Late Miocene (see Sage, 2017 for a summary), an era of global expansion of C 4 vegetation due to declining atmospheric CO 2 combined with global cooling and increase in climate seasonality and aridity(Cerling et al, 1997;Wen et al, 2023).The global maps of C 4 species richness (Figure2a-c) reveal two shared hotspots for C 4 grasses and C 4 eudicots: one in Mexico/ Southern United States and one in Australia. In these two regions, C 4 lineages seem to have diversified more intensively than in other parts of the world, and in case of the C 4 eudicots, this diversity has been recruited independently from multiple families and even multiple times within one family (Figures2e,f and 4c; Table2).…”
mentioning
confidence: 99%
“…However, stable isotope‐based reconstructions from pedogenic carbonate require an understanding of the carbonate forming system and whether there is a seasonal bias in carbonate formation (Breecker et al., 2009; Huth et al., 2019; Kelson et al., 2020; Methner et al., 2020; Page et al., 2019; Wen et al., 2023). For δ 13 C and δ 18 O, it has been well demonstrated that temperature and p CO 2 changes at depth in a soil profile are slow enough that the resulting carbonate compositions should be close to isotopic equilibrium with soil water and CO 2 (e.g., Cerling & Quade, 1993).…”
Section: Introductionmentioning
confidence: 99%